Pigment epithelium-derived factor upregulates collagen I and downregulates matrix metalloproteinase 2 in osteosarcoma cells, and colocalises to collagen I and heat shock protein 47 in fetal and adult bone - Alcantara, M.; Nemazannikova, N.; Elahy, M.; Dass, Crispin (John Wiley & Sons Ltd., 2014)
Objective: Pigment epithelium-derived factor (PEDF) has proven anti-osteosarcoma activity. However, the mechanism(s) underpinning its ability to reduce primary bone tumour (osteosarcoma) metastasis is unknown. Methods: Adult and fetal murine bone were immunostained for PEDF, collagen I (major protein in bone) and its processing proteins, heat shock protein 47 (HSP47, a chaperone protein for collagen I), membrane type I matrix metalloproteinase (MT1-MMP, a collagenase), and matrix metalloproteinase 2 (MMP-2, which is activated by MT1-MMP). Immunoblotting and immunocytochemistry were used to observe levels of the above biomarkers when human osteosarcoma cells were treated with PEDF. Key findings: Immunohistochemical staining in adult and fetal bone mirrors collagen I. PEDF localised to ridges of trabecular bone in tibial cortex and to megakaryocytes within bone marrow. Second, we observed that PEDF upregulates collagen I, HSP47 and MT1-MMP, while downregulating MMP-2 in osteosarcoma cells in vitro. Conclusion: PEDF is a promising antagonist to osteosarcoma cell metastasis via downregulation of MMP-2, and can induce tumour cells to further adopt differentiative properties, thereby possibly reducing their aggressive growth in vitro and in vivo.